2022
DOI: 10.3389/fcell.2022.893677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TP53 deficiency and KRAS signaling on the bioenergetics of colon cancer cells in response to different substrates: A single cell study

Abstract: Metabolic reprogramming is a hallmark of cancer. Somatic mutations in genes involved in oncogenic signaling pathways, including KRAS and TP53, rewire the metabolic machinery in cancer cells. We here set out to determine, at the single cell level, metabolic signatures in human colon cancer cells engineered to express combinations of activating KRAS gene mutations and TP53 gene deletions. Specifically, we explored how somatic mutations in these genes and substrate availability (lactate, glucose, substrate depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In addition, the studies by Spier et al and Monterisi et al highlight the role of mitochondrial function in cell fate and survival, emphasizing the interplay between metabolic and genetic factors in cancer therapeutics [31,32]. Kealey et al also highlight the complexity of cancer cell bioenergetics, as TP53 deficiency and KRAS signaling can alter cellular responses to various substrates, indicating that metabolic responses are multifaceted and context-dependent [33]. Collectively, our findings highlight the importance of an integrative approach that considers both genetic mutations and metabolic features in the development of targeted cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the studies by Spier et al and Monterisi et al highlight the role of mitochondrial function in cell fate and survival, emphasizing the interplay between metabolic and genetic factors in cancer therapeutics [31,32]. Kealey et al also highlight the complexity of cancer cell bioenergetics, as TP53 deficiency and KRAS signaling can alter cellular responses to various substrates, indicating that metabolic responses are multifaceted and context-dependent [33]. Collectively, our findings highlight the importance of an integrative approach that considers both genetic mutations and metabolic features in the development of targeted cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell infiltration is important for tumor progression; however, it is an underrated factor for evaluating the efficacy of ICI treatment ( 29 ). Increasing evidence has shown that the interaction between tumors and the microenvironment is critical for the progression of CRC and effectiveness of immunotherapy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%